Bringing adaptive management to life: Insights from practice - Arora, Anmol; Gogoi, Elizabeth; Joy, Divya; Kumar, Pankaj; Luthra, Rajni; Pal, Uma; Pervaiz, Arif (Oxford Policy Management, 2019)
The increasing popularity of adaptive programmes in the development sector in the past decade is partly a response to the complex and interconnected challenges facing many developing countries, including the impacts of climate change. The pathway to adapting to climate change is unknown, and there are many deep-rooted institutional, political, economic and social barriers. Adaptive programmes provide the flexibility to allow those delivering the technical assistance to support governments to experiment with different entry points and to adapt or change course when some are not successful. The Action on Climate Today (ACT) programme is a five-year adaptive programme that aims to strengthen systems of planning and delivery for adaptation to climate change in South Asia. As the programme draws to a close, this Learning Paper reflects on some of the major lessons learnt on the challenges and opportunities of using an adaptive programme management approach to support governments to adapt to climate change. The authors are members of the ACT implementation team, representing the management, operational and technical teams, from across different locations. The paper therefore reflects their first-hand account of the reality of implementing adaptive programmes. The paper sets out a framework for the essential ingredients of an adaptive programme management approach. These include a set of essential core principles: an evolving theory of change; a locally led and politically savvy delivery approach; experimentation and learning; and stakeholder alignment. It also includes two sets of essential resources required: management flexibility and adequate financial resources. The paper then provides learning from ACT on how to operationalise these core principles and mobilise the necessary resources. It gives detailed examples of challenges faced by ACT with regard to each component of the framework, and how the programme has overcome them, as well as retrospective reflections of additional actions the programme could have taken. A set of case studies unpacks how adaptive programme management has been operationalised in practice in particular locations. The authors are confident that the impact ACT has had owes in large part to it being an adaptive programme. The programme’s flexibility, decentralised structure and strong emphasis on learning have meant the team has been able to respond to opportunities as they have emerged and to invest time and resources where there was most potential for impact. However, this paper is also honest about the challenges ACT has faced as an adaptively managed programme. The paper therefore concludes with a set of lessons learnt from ACT for the benefit of others designing and delivering adaptive programmes on climate change and other issues.

Making adaptive rigour work - Principles and practices for strenghening monitoring, evaluation and learning for adaptive management - Ramalingam, Ben; Wild, Leni; Buffardi, Anne L (ODI/GLAM, 2019)
Adaptive programmes can be accountable, rigorous and high quality in how they use evidence by taking an ’adaptive rigour’ approach. Core development and humanitarian challenges are complex, and require processes of testing, learning and iteration to find solutions – adaptive management offers one approach for this. Yet large bureaucracies and development organisations can have low tolerance for experimentation and learning, and adaptive management can be viewed as an excuse for ‘making things up as you go along’. This briefing from the Global Learning for Adaptive Management (GLAM) initiative argues that adaptive programmes can be accountable, rigorous and high quality in how they use evidence – but this requires rethinking some key assumptions about how they are practised. The paper sets out three key elements of an ‘adaptive rigour’ approach: - Strengthening the quality of monitoring, evaluation and learning data and systems. - Ensuring appropriate investment in monitoring, evaluation and learning across the programme cycle. - Strengthening capacities and incentives to ensure the effective use of evidence and learning as part of decision-making, leading ultimately to improved effectiveness.

Adaptive Management Practice in the UK Government - The MUVA case - HLS (Human Learning Systems, 2019)
Case study about the MUVA programme in Mozambique. (Maybe it "misses the point of AP which is not learning for learning. Is learning for impact. The word impact doesn’t even come up once!") Adaptive Management programming within the Foreign & Commonwealth Development Office demonstrates that the UK Government has examples of optimising for learning within its existing management practice. However, currently, the adaptive management practices are unhelpfully framed by an approach which limits both their effectiveness and scope. The programmes use learning as their metastrategy. They succeed in connecting practicebased learning with strategic learning, and make a shift towards reframing accountability as accountability for learning. This learning strategy is enabled by funding and contract management arrangements which prioritise learning. Both at macro-level of programme management and micro level of de-risking experimentation and enabling necessary failure by decoupling people’s job security from potential failure.

Doing adaptive management at Sida - Tim Ruffer; Helen Bailey; Stefan Dahlgren; Patrick Spaven; Mark Winters (SIDA, 2019)
Lessons from the market systems development approach The evaluation focuses on Sida’s management of MSD projects. The projects are applying the MSD approach with an aim to: - contribute to improved MSD programming by Sida through better management practices across the project cycle - generate recommendations on how Sida can create conducive conditions for systems approaches and adaptive programming more generally. The brief assesses Sida’s organisational capacity for adaptive management in three dimensions: - leadership and culture - staff capacities - skills, and systems and procedures

The Case for an Adaptive Approach to Empowerment and Accountability Programming in Fragile Settings: Synthesis report - Christie, Angela; Green, Duncan (Itad, Oxfam and IDS, 2019)
Fragile, conflict and violence-affected settings (FCVAS) are messy and ambiguous contexts in which to plan and implement development initiatives. To work there, external actors are increasingly adopting an adaptive approach to empowerment and accountability (E&A) programming, whatever the setting. This means using a compass rather than map, where real-time political economy analysis (PEA) in relation to context and programme monitoring and evidence-informed learning in relation to intervention are used in combination and in shorter-than-usual planning cycles to maintain and adapt strategic direction. This paper brings together three case studies of large Department for International Development (DFID) governance projects in Myanmar, Nigeria and Tanzania.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of Institutions for Inclusive Development, Tanzania - Green, Duncan; Guijt, Irene (Itad, Oxfam and IDS, 2019)
Adaptive Management involves a dynamic interaction between three elements: delivery, programming and governance. This case study focuses on a large DfID governance project, the Institutions for Inclusive Development (I4ID), a five-year initiative in Tanzania. The study forms part of a research project to examine whether and how adaptive approaches can strengthen aid projects promoting empowerment and accountability in fragile, conflict and violence-affected settings (FCVAS). The research examines some of the assertions around the adaptive management approach and explores if and how adaptive approaches, including rapid learning and planning responses (fast feedback loops and agile programming) are particularly relevant and useful for citizen empowerment and government accountability (E&A) in FCVAS.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Agile Development in the Age of Adaptive Management - Davis, Taryn; Orton-Vipond, Sarah; Staid, Martha (Development Gateway, 2019)
Adaptive management – the idea that development projects should respond to real life complexities and be flexible enough to respond to unforeseen changes – is an often-praised approach to doing development differently, with donors and partners exploring how to apply it within their programming.

Implementing Adaptive Approaches in Real World Scenarios: A Nigeria Case Study, with Lessons for Theory and Practice - Bridges, Kate; Woolcock, Michael (The World Bank, 2019)
How does adaptive implementation work in practice? Drawing on extensive interviews and observations, this paper contrasts the ways in which an adaptive component of a major health care project was implemented in three program and three matched comparison states in Nigeria. The paper examines the bases on which claims and counterclaims about the effectiveness of these approaches were made by different actors, concluding that resolution requires any such claims to be grounded in a fit-for-purpose theory of change and evaluation strategy. The principles of adaptive development may be gaining broad acceptance, but a complex array of skills, expectations, political support, empirical measures, and administrative structures needs to be deftly integrated if demonstrably positive operational results are to be obtained, especially when undertaken within institutional systems, administrative logics, and political imperatives that are predisposed to serve rather different purposes.

Top Tips: How to design and manage adaptive programmes - Valters, Craig; Wild, Leni (Overseas Development Institute, 2019)
Within DFID, there is now a commitment to more flexible and adaptive programming. This recognises that: • DFID works in contexts that continuously evolve and change, sometimes in unpredictable ways. To respond to this, the agency needs to remain flexible – to expect change and have a good understanding of context, with resources that can be adjusted and scope to change direction if needed. All DFID programmes should be able to do this. • Some DFID programmes aim to support change in complex systems, behaviours and incentives. Efforts to address women’s empowerment, improve sanitation or build more sustainable health systems, for instance, all require engagement with the way in which complex systems operate and the people and behaviours within them. Trying to deliver reforms in these circumstances is challenging because the pathway to reform itself will be unclear: as a reform is rolled out, the system itself will react and respond. These types of programmes therefore need to build in from the start deliberate processes of learning and testing, to allow for adaptations as more information is gathered for what works over time. These top tips are concerned with programmes that aim to be flexible and adaptive – which work in dynamic contexts and are trying to address complex problems. While there is growing commitment to these approaches, feedback suggests staff still have questions about how to do this well. This document highlights some of the commonly reported issues related to adaptive programming and a set of tips, strategies and examples to help in addressing them. It is aimed at programme managers and advisors who may be Senior Responsible Owners (SROs) or those managing and supporting adaptive programming in a range of ways. We have collated these lessons from discussions with country offices and SROs, feedback from surveys and the wider evidence. We have looked specifically at the adaptive programmes we can find in the DFID portfolio, but this is not an exhaustive list. It should be noted that there is as yet no wide variety of case law to review, but there is a growing set of examples within DFID that can provide continuous learning for the organisation.

Monitoring and learning for country-level portfolio decision-making and adaptation - Buffardi, Anne L; Mason, Paige; Hutchings, Claire; Sharp, Samuel (ODI/GLAM, 2019)
Most measurement and adaptive management approaches were developed for and from individual projects. This briefing aims to guide measurement and management of country-level portfolios of work. It identifies potential purposes portfolio-level analyses can fulfil, types of adaptation, and the relative role of monitoring, learning and evaluation (MEL). Drawing on reviews of practice from the United States Agency for International Development (USAID) and the United Kingdom Department for International Development (DFID), guidance notes, and experiences of members of the Global Learning for Adaptive Management (GLAM) initiative, it offers recommendations and considerations that are particularly relevant for this level of analysis and management. Key messages - Portfolio-level analyses can serve eight potential purposes, each of which answers different questions, involves adaptation at different times and levels, and requires different types of evidence. Identifying the purpose(s) and how the component parts relate to each other should guide the development of monitoring and learning systems. - Portfolios are oriented more towards breadth than depth, involve more people with different perspectives, and draw on multiple sources of evidence with potentially greater variation in quality. - In practice, four activities appear to be applied most frequently at a portfolio level: alignment of indicators and aggregation of monitoring data; synthesis of multiple sources and types of information to provide a summary of outputs, outcomes, common observations and trends; periodic review and reflection sessions; and strategic planning, design or refresh of the portfolio strategy. - The extent to which evidence-informed portfolio management is facilitating learning and adaptation has not been well documented to date, and we suggest potential indicators to do so.

Monitoring and Result Measurement for Adaptive Programming - How to Use Data to Manage a MSD Program: Lessons from PRISMA - Khan, Khaled; Seely, Kevin; Ridwan, Mustika; Mulya, Bodhiya (PRISMA, 2019)
Using monitoring data to improve interventions is harder than it seems. Decision-makers are often busy implementing activities, unclear about their roles in data collection and analysis, and uncertain what data matters most or when. PRISMA, an AUD77 million agricultural Market Systems Development (MSD) programme funded by DFAT Australia, has encountered these challenges. With the programme completing its first five year phase, this case study shares ten key lessons divided into three sections: shaping the culture, developing systems, and top management decisions. These lessons aim to help program, sector and intervention managers make better use of monitoring data to improve interventions.

Help! I’m hiring new staff and I want them to work adaptively. A guide to hiring adaptive employees. - Salib, Monalisa (USAID LEARN, 2019)
If you are involved in hiring, this tool can help you increase your chances of selecting staff members skilled in adaptive management. It will help answer the questions: Which competencies should I recruit for in order to hire more adaptive employees? Which desired qualifications should I incorporate into position descriptions to attract adaptive employees? Which interview questions should I ask to screen for adaptive employee competencies? You should use this tool when you decide to hire a new individual - whether that be a direct hire, contractor, or consultant - or when you are changing an individual’s current position description or scope of work. Specifically, this tool will help you determine which qualifications are most important for the position and offers interview questions you can use with candidates. — You’re in luck! We just released a new guide for hiring adaptive employees. This visual and user-friendly tool will help increase your chances of selecting staff skilled in adaptive management. Here are the details: What do you mean by “work adaptively” or an “adaptive employee”? An adaptive employee is an individual who, in collaboration with relevant stakeholders, systematically acquires and uses knowledge to make decisions and adjustments in their work in order to achieve greater impact. Why focus on adaptive employees? Why does it matter? With industries, technologies, and organizations in a near constant state of flux, leaders are recognizing the importance of adaptability as a critical capacity. Because of this, it’s not surprising that a recent LinkedIn report found that adaptability was the most important soft skill hiring managers were screening for. In addition, evidence shows that teams that apply more data-driven and adaptive leadership practices perform better than those that focus less on these practices. It makes sense, then, that managers want to recruit more team members who are skilled in adaptive management - it helps achieve results. Who should use this tool? Anyone involved in hiring, responsible for developing or approving position descriptions, participating in interviews, and/or approving new hires. When should I use this tool? Use it as soon as you decide to hire a new staff person or when you’re adjusting existing position descriptions. What does the tool help me do? It will help you think through: Which competencies should I recruit for in order to hire more adaptive employees? Which desired qualifications should I incorporate into position descriptions to attract adaptive employees? (You can even copy and paste qualification language from the tool into scopes of work!) Which interview questions should I ask to screen for adaptive employee competencies? (You can copy and paste interview questions into your screening, interview, and reference check protocols!) Has the tool been tested? Yes, staff within USAID’s Global Development Lab and on the USAID LEARN contract tested the tool, providing feedback on the minimum viable product and subsequent versions. Testers confirmed finding the tool useful, and gave it a 9/10 score when asked if they would recommend it to colleagues. Some specific feedback from testers included: "The tool prompts deeper thought on what you might need and want in a job candidate" and "All [of the interview questions I used from the tool] worked well." What about the existing staff? How can they gain greater skills in adaptive management? Existing USAID staff and implementing partners can access online training in collaborating, learning, and adapting (CLA) and find resources in the CLA Toolkit. USAID staff also have access to an internal CLA community of practice and five-day, in-person CLA training.

Adaptive Management - Jenal, Marcus; Cunningham, Shawn (Annual Reflection 2019, 2019)

Summer school on Adaptive Management - 2019 - CID (2019)
General description of the curriculum

Short Course - Adaptive Management, an overview - Bazaz Smith, Komal (American University, 2019)

Managing staff transistions through CLA: preserving institutional memory as staff come and go - USAID (USAID LEARN, 2019)
This document is relevant for any position or hiring mechanism. While this document does not explicitly address what happens when someone arrives into a newly-created position, which has its own set of challenges, many of the principles, actions, and resources can be applied in that context. Section 1 offers guidance for how to set up and implement systems at Mission/OU or office to ensure that all staff help preserve institutional memory and enable continuity of relationships. This section is for any staff in a Mission/OU working to build systems that improve handovers and knowledge capture and sharing across the Mission or OU. If a Mission or OU is just beginning to develop a system to manage staff transitions, you may want to start by developing a system within an office or team and then expand it out to other offices or to the Mission/OU writ large. Section 2 includes key principles and actions individuals could consider following when arriving or departing a position, regardless of hiring mechanism and position. This includes staff new to the Mission/OU and staff who are currently in the Mission/OU and are moving into a new position. Section 3 provides a select number of resources to help you take a systematic and comprehensive approach to manage staff transitions as effectively and efficiently as possible at the individual or organizational level.

Scrambling after Moving Targets: Monitoring & Evaluation Applied to Adaptive Management Approaches in Peacebuilding - Woodrow, Peter; Jean, Isabella (New Directions in Peacebuilding Evaluation, 2019)
In this landmark collection, the voices of pathMakers and innovators in peacebuilding evaluation are assembled to provide new direction for the field.
Keywords: IMPORTANT

How DFID can better manage complexity in development programming - Sharp, Samuel; Valters, Craig; Whitty, Brendan (ODI, 2019)
The United Kingdom’s (UK) Department for International Development (DFID) is an ambitious government department that is committed to reducing poverty and conflict overseas. Many of the issues on which DFID works are complex; whether focused on climate change, gender equality, health or other priorities, simple solutions rarely exist. And to tackle these complex challenges, DFID staff must interact with unpredictable systems of political, organisational and individual behaviours and incentives. There is a risk that complex problems spur more complicated programmes; that the complexity of development challenges is addressed through designing programmes with too many projects and implementers. While there may be valid reasons for this, too many of these complicated programmes will overburden staff. This briefing note is the outcome of an ongoing process within DFID to confront these issues and answer the question: how can DFID design and manage programmes to address complex development challenges without creating too much staff workload? Key messages DFID deals with complex problems, which require flexible systems to support testing, learning and adaptation. • Complex problems do not necessarily require workload-heavy delivery structures, but simpler approaches depend on delivery partners’ experience and competence. • However, programmes that tackle complex problems do require more hands-on engagement and face more workload from inflexible compliance requirements. We suggest that DFID and similar agencies: • Pay closer attention to delivery options in programme design, making use of existing options where possible and, where not, fostering local organisations through long-term investments. • Encourage programme designers to articulate how ambition matches resources and consider ‘good enough’ design. • Reduce the burden of compliance by cultivating partner autonomy, reassessing results and valuefor-money requirements and promoting more flexible contracting and procurement. • Plan and prioritise management resources across a portfolio of programmes to make sure they can be focused in the right areas, where the complexity of the problem requires greater engagement.

Paradoxes and partnerships: a study of knowledge exploration and exploitation in international development programmes - Lannon, John; Walsh, John N. (Journal of Knowledge Management, 2019)
Purpose – This paper aims to look at how organisational partnerships balance knowledge exploration and exploitation in contexts that are rife with paradoxes. It draws on paradox theory to examine the partnership’s response to the explore-exploit relationship.

Planning & Navigating Social Change - Tools for Pacific voyagers - Orr, Douglas Epeli; Cavatore, Maria; Aston, Tom (Oxfam, 2019)
Those working to advance social change in the Pacific must understand, work with and respond to the complex and changing relationships and dynamics of power that exist within such networks, and situate their work in the context of decolonisation and self-determination. But the approaches typically used by NGOs to plan our projects and programs have failed to give due attention to these dynamics. The result is that our projects fall short of achieving their promise, despite being technically sound and logical. In this guide, we aim to provide a process and tools that prioritise and draw out the rich, often implicit, knowledge that Pacific Islanders have about our contexts to plan and manage social change initiatives in a manner that values and responds to this ocean of relationships. Drawing from these relationship-based and voyaging traditions, we emphasise the need to: • frame change in terms of change in people; e.g. change in the situation of groups of people and change in terms of the actions of people; • identify a course towards a particular ‘change destination’; • identify the signs to read that will help you determine where you are on that course; • be constantly attentive to the context as you make the journey, and • be ready to adjust your course in response to changes in your context. To support this way of working, we have selected a number of tools from approaches that we believe fit. In particular, we have drawn from the following approaches: • Thinking and Working Politically and other ‘politically aware’ approaches that recognise that the success of a development initiative will be determined by the interplay of relationships of power within a particular context, not just by having the right technical solution; • Outcome mapping because of its focus on people and relationships, and on identifying and supporting needed changes in the behaviour of specific actors in relation to others. This is key, because it’s individuals who deliver services, individuals who decide whether to allocate budget and resources to address a problem, and individuals who make the choice to believe whether a service is relevant to solving their issues; • Adaptive management because of its recognition that development initiatives take place within complex and changing systems and need to adjust to these and that this requires ongoing learning and adaptation.

A Guide to Digital Feedback Loops. An approach to strengthening program outcomes through data for decision making - Whittle, Dennis; Campbell, Megan (USAID, 2019)
Feedback is information about what happens as a result of what you do. Using that information to adapt what you do or how you do it creates what is called a feedback loop. A digital feedback loop uses digital technology at some stage of the feedback loop. Digital feedback loops help USAID missions improve the effectiveness and efficiency of their activities and can support partner countries on their journey to self-reliance through increased information sharing and improved government and civil society capacity. USAID missions and their partners have used digital feedback loops to improve HIV treatment targeting in Zimbabwe, engage three million young people in Nigeria in policy, and reduce field reporting times from one month to one day. Digital feedback loops provide access to information faster and more cheaply than ever before. As part of an adaptive management approach, digital feedback loops increase our ability to act on opportunities and respond to challenges. That in turn can improve outcomes and reduce the risk of waste and failure. This guide outlines the case for integrating digital feedback loops into your work, and provides tools, resources and guiding questions to support you as you get started. The guide includes examples of how USAID missions are using digital feedback loops to improve their programs in various sectors and provides worksheets to help you apply digital feedback loops to your own context.

The Rapid Evaluation, Action, and Learning (REAL) Approach: A toolkit to measure and refine changes and interventions in health campaigns - PATH (PATH, 2019)
Evaluative Tools for Improving Campaign Effectiveness Public health campaigns aim to control disease or deliver essential health services and products through time-limited and periodic channels. Many countries use campaigns to augment or replace routine service delivery, to target certain populations, or to accelerate progress towards coverage targets. The Root Cause Analysis and Rapid Evaluation, Action, and Learning toolkits present a systematic but flexible approach to identifying the root causes of campaign bottlenecks and then designing, testing, and refining solutions to optimize potential impact. These toolkits respond to a growing need for “fit-for-purpose” rapid-testing, adaptive learning approaches to evaluation and the need for a culture shift toward iterative adaptation and improvement that integrates measurement and evidence-informed decision-making into daily practice. The comprehensive package of toolkits, in addition to the individual Root Cause Analysis toolkit and Rapid Evaluation, Action, and Learning toolkit are available below.

Thinking and Working Politically: Learning from practice. Overview to Special Issue - McCulloch, Neil; Piron, Laure-Hélène (Development Policy Review, 2019)
Over the last 15 years, a set of ideas now referred to as “thinking and working politically” (TWP) has coalesced into a “second orthodoxy” about how to take context into account when implementing development interventions. This approach stresses the importance of obtaining a better understanding of the local context (“thinking politically”) in order to support local actors to bring about sustainable developmental change (“working politically”). However, the evidence base to justify this new approach remains thin, despite a growing number of programmes which purport to be implementing it. Officials in development agencies struggle with putting it into practice and it is unclear how TWP differs—or not—from similar approaches, such as Problem Driven Iterative Adaptation (PDIA) and Doing Development Differently (DDD). This Special Issue sheds light on what TWP means in practice by examining a set of initiatives undertaken by both development partners and government departments in Nigeria, the Occupied Palestinian Territories, China and India. This overview article outlines, in brief, each of the Special Issue's four papers and then draws out five lessons—for funders and for practitioners—from across all the papers. Our five lessons are: (1) the fundamental importance of undertaking political economy analysis (PEA) to adapt programmes to their contexts; (2) the importance of having a realistic level of ambition for interventions; (3) the need to support local ownership—not just “agreement ownership” (between a donor agency and government) or local “management ownership” of the programme, but critically “driver ownership” by generating trust with the key local actors driving change; (4) the need for a more effective set of tools for measuring results in complex programmes that attempt to achieve improvements in long-run governance; and, (5) that although the political economy of donors is often seen as a barrier to applying TWP, the articles show how much can be done with a TWP approach if the analysis takes into account the political economy of donors as well as that of the local context. We conclude with a set of operational recommendations for donors and implementors, as well as suggestions of avenues for further research.
Keywords: Adaptation; Development programmes; Political economy analysis; Reform space; thinking and working politically

Barrio Mio and Katye: PCI’s neighbourhood approach in cities - Campbell, Leah (ALNAP/ODI, 2019)

AID Programming Guide - DFAT (Australian Government, 2019)

Knowledge Retention and Transfer (KRT) - Model and Matsurity Matrix - USAID (USAID LEARN, 2019)
The Maturity Matrix is not a standalone tool. It is one of the three major components of the KRT Model. The Maturity Matrix is meant to be used in conjunction with the KRT Toolkit and Implementation Plan.

Evaluation of development programmes - OECD - OECD (2019)
Data & research on evaluation of development programmes inc. paris declaration, budget support, multilateral effectiveness, impact evaluation, joint evaluations, governance, aid for trade

Thinking and Working Politically in Economic Development Programmes – Some Sprints and Stumbles from a DFID Programme in Kyrgyzstan - Koleros, Andrew; Rinnert, David (From Poverty to Power, 2019)
A DFID programme in Kyrgyzstan offers useful insights into how the Thinking and Working Politically approach can escape from its governance ghetto
Keywords: Case Study

Failing Forward: How CARE is focusing on what goes wrong to improve impact - Janoch, Emily (USAID LEARN, 2019)
CARE's Failing Forward initiative is sparking opportunities to showcase the ideas that don't work so we can spend more time implementing the ones that do. It's changing the conversation inside the organization, and leading to changes in the way we design and implement programs. It's also allowing us to make connections across a global portfolio of more than 900 projects, and with new and different partners to learn from their experience.

How Does the World Bank Build Citizen Engagement Commitments into Project Design? Results from Pilot Assessments in Mozambique, Myanmar, Nigeria, and Pakistan - Nadelman, Rachel; Le, Ha; Sah, Anjali (IDS, 2019)
How and to what degree is the World Bank putting its new institutional citizen engagement (CE) commitments into practice? This question guides an independent assessment that the Accountability Research Center (ARC) at American University has undertaken as part of the Institute of Development Studies-led Action for Empowerment and Accountability (A4EA) research programme’s investigation into how external actors can best support local processes of and conditions for empowerment and accountability. This report investigates the World Bank’s incorporation of CE into project design, the critical early stage of donor engagement. To accomplish this, ARC reviewed the World Bank’s fiscal year 2015–17 investment project portfolios for four A4EA priority countries, Mozambique, Myanmar, Nigeria, and Pakistan, which covers 57 projects that range from US$19 million to U$600 million. The analysis determines whether projects commit to seeking a strategic approach to CE, which involves combining multiple tactics so that the whole could be greater than the sum of the parts. This assessment of CE commitments is intended to help to inform possible national, civil society organisation strategies to monitor whether and how these commitments are actually implemented in practice.

How We Model Matters: A Manifesto for the Next Generation of Program Theorizing - Whynot, Jane; Lemire, Sebastian; Montague, Steve (Canadian Journal of Program Evaluation, 2019)
In this concluding article, grounded on the exemplary contributions contained in the preceding pages, the guest editors scale the proverbial soapbox and present a manifesto to guide the pursuit and advancement of the next generation of program theorizing. Formulating ten declarations for program theory development and examination, the modest hope of the authors is to motivate and inspire reflective evaluation practitioners to broaden their views, approaches, and techniques for future program theorizing.